EFFECT OF STRAW MULCH AND ANTI- W MULCH AND ANTI-TRANSPIRANTS ON YIELD AND QUALITY OF SOYBEAN (GLYCINE MAX L. MERRIL) . MERRIL) - JAMIR, MLIWATI; SINGH, A .K; JAMIR, ZULUTEMJEN; AO, ENGRALA (The Bioscan, 2024)
A field experiment was conducted for three consecutive years during kharif season to assess the effect of straw mulch and anti-transpirants on growth, yield and quality of soybean. Straw mulch application @ 5 tons ha-1 resulted in significantly higher N, P and K content in grain, seed protein content, seed, stover and biological yield and harvest index. Foliar application of Glycerol 5% as anti-transpirant resulted in significantly higher seed yield and harvest index but for N, P and K content in seed, protein content and available N and K in soil anti-trans pirants did not show significant difference. All the treatments in which mulch was included proved to be superior. The highest seed yield (2347 kg ha-1), stover yield (2736 kg ha-1) and biological yield (5083.6 kg ha-1) was recorded in M1A3 [mulch + Sodium carbonate (Na2 CO3 ) 5%]. However, the highest harvest index was observed in M1A2 [mulch + Glycerol 5%] (47.51 %). M1A1 [mulch + Magnesium carbonate (MgCO3) 5%] gave the highest N content and highest protein content in seeds. Available N and P in soil was recorded to be the highest in M1 A2 [mulch + Glycerol 5%] with 283 kg ha-1and M1A0 [mulch + control] 17.27 kg ha